Lending of Electronic Books by Public Libraries Under European Union Law - Janković, Nemanja (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2026)
Public libraries in the European Union are recognized as important institutions that provide citizens with access to art, science, and objective information. In all EU Member States, public libraries enjoy a privileged position due to the public function they perform. For centuries, one of the core services offered by libraries has been the lending of books. In recent decades, owing to the process of mass digitization, electronic books have become increasingly popular among readers. Consequently, the question has arisen as to whether the lending of electronic books by public libraries is legally permissible. The first part of this paper is dedicated precisely to these issues: the position of public libraries in the European Union, the concept of electronic books, and the legal right of public libraries to lend books. The dilemma concerning the permissibility of e-book lending was resolved by the Court of Justice of the European Union in its 2016 judgment in Vereniging Openbare Bibliotheken (VOB), where the Court held that the lending of electronic books is permissible under certain conditions. Subsequently, in its 2019 judgment in Tom Kabinet, the Court of Justice of the European Union imposed an additional restriction regarding the lending of electronic books by public libraries. In the second part of the paper, the author analyzes these CJEU judgments and highlights best practices established in the Kingdom of the Netherlands.